PENGARUH TOTAL QUALITY MANAGEMENT (TQM) , PARTISIPASI ANGGARAN , DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL : STUDI EMPIRIS PADA KANTOR IMIGRASI KELAS I TPI SURAKARTA - Muhammad Ferdinan Widyatama; Hudi Kurniawanto (Nirta Learning Centre, 2026)
This research aims to analyze the influence of Total Quality Management (TQM), budgetary participation, and reward systems on managerial performance at the Class I Immigration Office TPI Surakarta. This study is an empirical study employing a quantitative approach. The population consisted of all employees at the Class I Immigration Office TPI Surakarta, with a total sample of 77 respondents determined through a saturated sampling (census) technique. Data were collected using questionnaires and analyzed using multiple linear regression. The results indicate that Total Quality Management (TQM) and reward systems have a positive and significant effect on managerial performance. Conversely, budgetary participation does not have a significant impact on managerial performance at the Class I Immigration Office TPI Surakarta. However, limited access and the relatively specific sample size within a single organizational sector mean that the findings cannot be widely generalized to other industries or business sectors with different organizational cultures and bureaucratic structures.